EFFICIENCY INCREASE OF NON-STICK COVERINGS OF CASTING MOLDS - A. V. Bataychuk; V. V. Mudryj; Yu. A. Nikolaychik (Литьë и металлургия)
Matters of efficiency increase of antipenetration washes of casting molds by application in their compositions the nanostructured modifiers having higher catalytic and reactionary ability that enables to intensify primary and secondary synthesis of high-heat-resistant phase in antipenetration wash are considered.